THE CONCEPT OF SUPPLY CHAIN MANAGEMENT AS A METHOD OF OPTIMIZING THE DOING BUSINESS (Journal of Economic Research & Business Administration, 2018)
The article considers the recognition of many leading specialists in supply chain management, that the concept of Supply Chain Management (SCM) is one of the most effective ways to manage commercial structures, which significantly improve the optimization of business conduct.To improve the efficiency of the company, the company must apply the concept of SCM to facilitate the synchronization of all activities carried out during production and distribution; Value added value optimization (VAL) for the end user; elimination of ineffective business activities.Currently, the concept of supply chain management is associated not only with maximizing the productivity and profitability of individual business units of the chain, but with optimizing the entire system to achieve higher quality of service at lower total costs.